Efektivitas Pembelajaran Menggunakan Metode Resitasi Terhadap Hasil Belajar IPS Peserta Didik - Hartinawanti, Hartinawanti (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to determine the effectiveness of learning by using the recitation method on the social studies learning outcomes of students at SD Negeri 2 Wonco. Methods This research uses a quantitative approach to the type of experimental research and the design of this study uses a quasi-experiment design. Data collection techniques through questionnaires and documentation. The population is all students of SD Negeri 2 Wonco, totaling 136 odd semesters for the 2021/2022 academic year. The sampling technique used was purposive sampling so that a sample of 40 people was determined and the group was divided heterogeneously. The data analysis technique used descriptive statistics and inferential statistics. The results showed that the implementation of learning using the recitation method was proven to have an effect on the social studies learning outcomes of fifth grade students of SD Negeri 2 Wonco. There is a significant difference between learning outcomes before the action is taken and after the action is taken so that the implementation of learning using the recitation method is effective on social studies learning outcomes for class V SD Negeri 2 Wonco.